Gel‐type emulsified muscle products: Mechanisms, affecting factors, and applications. Issue 6 (27th October 2022) - Zhu, Shichen; Zhu, Hao; Xu, Siyao; Lv, Shuangbao; Liu, Shulai; Ding, Yuting; Zhou, Xuxia
Abstract: The gel‐type emulsified muscle products improve fatty acid composition, maintain the oxidative stability, and achieve a better sensory acceptability. This review emphasizes the stabilization mechanisms of these emulsified muscle products. In particular, factors associated with the stability of the emulsified muscle systems are outlined, including the processing conditions (pH and heating), lipids, and emulsifiers. Besides, some novel systems are further introduced, including the Pickering emulsions and organogels, due to their great potential in stabilizing emulsified gels. Moreover, the promising prospects of emulsion muscle products such as improved gel properties, oxidative stability, freeze–thaw stability, fat replacement, and nutraceutical encapsulation were elaborated. This review comprehensively illustrates the considerations on developing gel‐type emulsified products and provides inspiration for the rational design of emulsified muscle formulations with both oxidatively stable and organoleptically acceptable performance.